Evaluation of Project GTR (Gravitational Teaching Resource) as an Instructional Material for the General Theory of Relativity - Jhon Dave Larra; Danisse M. Barrera; Lovelyn J. Bayadas; Christian A. Ellipse; Reyden D. Lumanas; Josh Railey R. Valdez; Faith Celeste B. Ole (Scientia Publica Media, 2026)
Physics is a fundamental science that explores complex and abstract concepts, often presenting significant cognitive challenges for learners. Topics such as Einstein’s General Theory of Relativity, specifically spacetime curvature and gravitational lensing, are difficult to grasp through traditional, lecture-based teaching methods. Prior studies have established that integrating tactile physical models, visual analogies, and digital simulations can significantly bridge this gap and enhance conceptual understanding. Building on this theoretical foundation, the present action research evaluates the effectiveness and acceptability of Project GTR (Gravitational Teaching Resource). This innovative instructional material purposefully combines these pedagogical tools, using a multisensory setup to model celestial bodies and light distortion, to improve students’ spatial and conceptual comprehension of gravitational lensing. The study involved thirty-seven students and three science teachers from a state university in the Negros Island Region, utilizing convenience sampling. To provide a comprehensive evaluation, a mixed-methods approach was carefully employed. Quantitative data were gathered through an adapted evaluation instrument measuring content and technical quality, while qualitative insights were systematically collected via participant feedback forms, structured interviews, and direct classroom observations. The quantitative results demonstrated a very high level of acceptability for Project GTR in both its content quality (M = 4.91, SD = 0.26) and instructional and technical design (M = 4.91, SD = 0.25). Furthermore, thematic analysis of the qualitative data revealed a marked increase in student engagement, a much deeper conceptual understanding of relativity, and highly positive attitudes toward learning physics. Ultimately, these findings underscore the significant potential of localized, multisensory, and interactive tools to transform abstract physics education and promote highly meaningful learning outcomes.